PERAN GURU DALAM MEMBANGUN KARAKTER ANAK USIA DINI ERA MODERN DI TAMAN KANAK-KANAK NEGERI 15 MENDALO DARAT KABUPATEN MUARO JAMBI PROVINSI JAMBI - Nazila; Jamilah; Sapriya Utami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This thesis discusses the role of teachers in building the character of early childhood. This research was conducted at State Kindergarten 15 Mendalo Darat, Muaro Jambi Regency, Jambi Province. The purpose of this study was to determine how teachers build the character of early childhood, how to overcome obstacles in building the character of early childhood and what are the obstacles in building the character of early childhood. This research is a qualitative study, data collection was carried out by means of observation, interviews, and documentation to determine the role of teachers in building the character of early childhood. The results of the study showed that the role of teachers in building the character of early childhood in the modern era at State Kindergarten 15 Mendalo Darat, Muaro Jambi Regency, Jambi Province is as follows: First, teachers as informants, namely teachers can be a source of information in working together with friends. Second, teachers as motivators, namely teachers can motivate children to share with their friends. Third, teachers as initiators, namely teachers can teach in giving and answering greetings well. Fourth, teachers as facilitators, namely teachers create a pleasant learning atmosphere and make children obey the rules of the game. Fifth, teachers as evaluators, namely teachers give awards in learning.